Effect of Dolutegravir Functional Monotherapy on HIV-1 Virological Response in Integrase Strand Transfer Inhibitor Resistant Patients. Issue 6 (August 2016) - Naeger, Lisa K; Harrington, Patrick; Komatsu, Takashi; Deming, Damon
Background: VIKING-4 assessed the safety and efficacy of dolutegravir in heavily antiretroviral treatment-experienced patients who had documented integrase strand transfer inhibitor (INSTI) resistance-associated substitutions in their HIV. VIKING-4 had a placebo-controlled 7-day dolutegravir functional monotherapy phase followed by dolutegravir plus an optimized background regimen for 48 weeks. Methods: Independent resistance analyses evaluated week 48 virological responses in the VIKING-4 trial based on the presence of baseline INSTI resistance-associated substitutions and baseline dolutegravir phenotypic susceptibility. Response rates at week 48 based on baseline dolutegravir resistance subgroups were compared for the 7-day dolutegravir functional monotherapy arm and placebo-control arm. Additionally, genotypic and phenotypic resistance at day 8 and time of failure was analysed for the virological failures from both arms. Results: Week 48 response rates for VIKING-4 were 23% (3/13) in the 7-day dolutegravir functional monotherapy arm compared with 60% (9/15) in the 7-day placebo arm. Response rates were consistently lower in the dolutegravir functional monotherapy arm across baseline INSTI genotypic and phenotypic subgroups. There was a higher proportion of virological failures in the 7-day dolutegravir functional monotherapy arm ( n =6/13; 46%) compared with the 7-day placebo arm ( n =3/15; 20%). Additionally, five virological failures in the dolutegravir arm had virus expressing emergent INSTI resistance-associated substitutions compared with two in the placebo arm. Conclusions: Analysis of response rates and resistance emergence in VIKING-4 suggests careful consideration should be given to the duration of functional monotherapy in future studies of highly treatment-experienced patients to reduce the risk of resistance and virological failure.